Evaluasi Kesesuaian Lahan untuk Budidaya Durian Bawor di Kabupaten Banyumas Menggunakan SIG Berbasis IoT - Luthfi Wahab; Anri Kurniawan; Hanis Adila Lestari (Jurnal Ilmiah Rekayasa Pertanian dan Biosistem, 2025)
Durian, known as the "King of Fruits," is a prevalent fruit in Indonesia, thriving in the tropical climate of Southeast Asia. One of the most widely cultivated varieties is Bawor, commonly found in Banyumas Regency, Central Java, producing 95,426 quintals in 2024. The price of Bawor durians ranges between Rp. 85,000 to Rp. 120,000 per fruit, weighing between 2 to 4 kg. Durian grows optimally in lowland areas up to 180 meters above sea level, with a humid climate, air temperatures of 25-32°C, humidity levels of 50-80%, and sunlight intensity of 45-50%. The research aims to build an information system called "SiDurIoT" based on the Internet of Things (IoT) integrated with a Geographic Information System (GIS) to evaluate the suitability of Bawor durian land. Land evaluation is classified S1, S2, S3, and N. Durian Information System with Internet of Things "SiDurIoT" is a device designed to measure the suitability of durian orchards in real-time. The device consists of a DHT22 sensor, a wind speed sensor, and GPS connected to the ESP32, with data displayed on an LCD screen. The device is connected to the internet via the website siduriot.my.id and the "SiDurIoT" smartphone application, which allows users to input measurement data. The results of the land suitability assessment show that wind speed, rainfall, soil pH, soil temperature, and land elevation are highly suitable (S1). In contrast, air temperature is suitable (S2), and humidity and sunlight intensity are marginally suitable (S3). Based on the suitability evaluation, the Kemranjen, Sumpiuh and Tambak areas are the most suitable locations for durian plantations because they have productivity above 10,000 quintals and are very suitable (S1).